Customer Relationship Management (CRM) in Modern Retail: A Bibliometric Study - Judijanto, Loso (West Science Business and Management, 2025)
Customer Relationship Management (CRM) has emerged as a strategic cornerstone for modern retail, driven by the dual forces of customer-centric business models and digital transformation. This study conducts a bibliometric analysis to map the intellectual structure, research trends, and thematic evolution of CRM in the retail sector. Using the Scopus database, publications from 2000 to 2025 were retrieved and analyzed with VOSviewer, producing co-authorship, co-citation, and keyword co-occurrence visualizations. The findings reveal that traditional themes such as customer satisfaction, loyalty, and public relations remain central to CRM research, while newer areas such as artificial intelligence, machine learning, big data, and e-commerce have emerged as critical enablers of CRM innovation. The analysis further highlights the dominance of the United States, the United Kingdom, and India as major contributors, alongside strong collaborations across Europe and Asia. Theoretically, this study consolidates fragmented insights across marketing, management, and information systems, situating CRM within the broader paradigm of digital business ecosystems. Practically, it provides retailers with guidance on aligning relationship-building strategies with data-driven technologies to achieve competitive advantage. While limited by database coverage and language scope, the study offers valuable directions for future research, emphasizing interdisciplinary collaboration and the integration of advanced analytics into CRM practices.